Flame retardancy of biodegradable polylactic acid with piperazine pyrophosphate and melamine cyanurate as flame retardant. (July 2022) - Chen, Hongxu; Xia, Wei; Wang, Nan; Liu, Yang; Fan, Penghui; Wang, Song; Li, Sanxi; Liu, Jie; Tang, Tao; Zhang, Ailing; Ding, Zhan; Wu, Weidong; et al.
A flame-retardant polylactic acid composite added with piperazine pyrophosphate and melamine cyanurate was developed. Piperazine pyrophosphate and melamine cyanurate showed synergistic effect in the polylactic acid composites. When the weight ratio of piperazine pyrophosphate to melamine cyanurate was 4:1 and the loading of the piperazine pyrophosphate/melamine cyanurate flame retardant was 15 wt.%, the prepared polylactic acid composites passed V-0 rating in the UL-94 test and achieved the high limit oxygen index value of 34.9%. The cone calorimeter test result confirmed that the addition of piperazine pyrophosphate/melamine cyanurate flame retardant reduced the total heat release value of polylactic acid. The effect of polylactic acid biodegradation on the flame retardancy of polylactic acid composite was further discussed. The biodegraded polylactic acid, which was exposed to the air for 8 months, showed high flame retardancy and even passed V-0 rating in the UL-94 test without the addition of piperazine pyrophosphate/melamine cyanurate flame retardant, which proved that biodegradation could affect the flame retardancy of polylactic acid.